Report Of Business Plan ENT 300 : Liplous Kiss / Siti Salwa Husain - Husain, Siti Salwa (2020)
The product that I was offered to my customer was any type of lip cosmetics such as lipstick, lip mate, lip tint and also lip balm. The reason why I choose to make my own brand of lips cosmetic is to fulfil my criteria and suit my lips which are worth to Asian people. The best part of my lipstick is we are using honey and lemon to all of our lipstick either lips mate, lip tint or lip balm. We make this lipstick to be fair as men also can wear our lipstick. This helps to improve our lips. Just like lime, lemon can also eliminate the dark colour on the lips so that red lips appear natural. Lemon is often used to counteract dark spots or spots on the skin. I named my lipstick is Lipslous Lipstick. The benefits of the glow in the lemon content can help brighten the colour of the lips. Honey is also powerful in normalizing the texture of the lips to make it smoother and less fragile. Because honey contains many vitamin B, calcium, sodium, iron, or potassium nutrients that are good for lip health. Yes, a healthy lip also helps make the lips look natural. In addition, the use of honey as a mask on the lips is very effective in eliminating bacteria. The anti-bacterial content is able to heal the wounds on the lips which usually occur due to broken skin of the lips. Lips are the most attractive part on our face than the other part. Lipstick has a rich and colourful history. Throughout history, women have always worn lipstick to make them more noticeable and attractive. Lipstick draws attention to the lips and makes them stand out. Lips are considered a sensual part of the body, and highlighting them can make women more attractive to the opposite sex. Some women may wear lipstick to feel better about their appearance. Other women enjoy the ability to express their unique artistic style. Colours and ingredients have changed over the centuries, but the purpose for wearing lipstick remains the same: to express inner beauty with outer self. The wonderful thing about lipstick is the sheer variety and versatility in colour and composition.